A fractionation strategy of cellulose, hemicellulose, and lignin from wheat straw via the biphasic pretreatment for biomass valorization. (May 2023) - Zhan, Qiwen; Lin, Qixuan; Wu, Yue; Liu, Yao; Wang, Xingjie; Ren, Junli
Graphical abstract: Highlights: The p-TsOH/2-MeTHF/H2 O system was desirable for high selectivity fractionation. 95.69% cellulose was retained as high removal of hemicellulose and lignin. The hydrolysate was dehydrated into 80.07% furfural in the biphasic system. The digestibility of residue was achieved at 95.82%. 33.83% precipitated lignin could be obtained based on raw material. Abstract: Developing an environmentally friendly and efficient pretreatment to utilize wheat straw is essential to a sustainable future. An acid biphasic system with 2-methyltetrahydrofuran (2-MeTHF) organic solvent and dilute p-toluenesulfonic acid (p-TsOH) were employed for the simultaneous fractionation of three components. Results showed that the biphasic system had excellent cellulose protection and high removal of hemicellulose and lignin. In detail, Under the optimal conditions (0.1 M p-TsOH, 2-MeTHF: H2 O = 1:1 (v:v), 140 °C, 3 h), mostly cellulose retained in the residues (95.69%), 57.18% of lignin was removed and high yield of hemicellulose-based C5 sugars was achieved (77.49%). In the further process of dehydration of pre-hydrolysate dichloromethane (DCM) as an organic phase, the yield of furfural was 80.07% (170 °C–80 min). The saccharification of residue reached 95.82%. p-TsOH/2-MeTHF/H2 O pretreatment was desirable for high selectivity fractionation. Important chemicals for bioenergy including furfural, monosaccharides and lignin are obtained.